Information security and privacy 16th Australasian Conference, ACISP 2011, Melbourne, Australia, July 11-13, 2011. Proceedings - Parampalli, Udaya; Hawkes, Philip (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 16th Australasian Conference on Information Security and Privacy, ACISP 2011, held in Melbourne, Australia, in July 2011. The 24 revised full papers presented  together with an invited talk and 9 poster papers were carefully reviewed and selected from 103 submissions. The papers are organized in topical sections on symmetric key cryptography, hash functions, cryptographic protocols, access control and security, and public key cryptography.